Perú, cambio climático y enfermedades no trasmisibles: ¿dónde estamos y a dónde vamos? - Avilez, J.L., Bazalar, J., Azanedo, D. and Miranda, J.J. (My University, 2016)
The world is facing a crisis of noncommunicable diseases alongside a state of climate volatility. Of the total health burden attributable to climate change, 99% will be assumed by developing countries. In light of climate change, Peru&rsquos best opportunity is to create mitigation and adaptation policies focused on developing health co-benefits, which will improve the state of noncommunicable diseases and the climate system. This article presents Peru&rsquos compromises in terms of mitigation of greenhouse gas emissions identifies public health opportunities for Peru under the Paris Agreement signed in the 21st Conference of the Parties (COP21) and makes recommendations for evidence and policy generation for the National Academy of Medicine and the Peruvian government.
Keywords: Cambio climático, Enfermedad crónica, Política de salud, Perú